Periodontal disease and perinatal outcomes: a case-control study - D. G. Bassani (Blackwell Synergy, 2007)
Aim: Our aim was to measure the association of maternal periodontitis with low birth weight (LBW), pre-term LBW, and intra-uterine growth restriction. Material and Methods: An inclusive case–control design including subjects examined for periodontitis through attachment loss, information on perinatal outcomes and general health. Data were analysed through conditional logistic regression. Results: Cases (n5304) and controls (n5611) had similar prevalence and severity of periodontitis, defined as at least three sites, in different teeth, with loss of three or more millimetres of clinical attachment level. Several factors were associated with the outcome, but the crude odds ratio for periodontitis was not significant. Odds ratio were 0.93 [95% confidence interval (CI): 0.63–1.41] for LBW and 0.92 (95% CI:0.54–1.57) for pre-term LBW in the presence of periodontitis, after adjustment for maternal age, previous pregnancies, pre-natal care, smoking, previous low birth or premature birth and other medical conditions, on a hierarchical model. Conclusions: Results do not support the hypothesis of association observed in previous studies after appropriate controlling for confounding variables. Negative perinatal outcomes are better explained by determinants other than periodontal health. This study adds to the growing body of literature on the relationship between periodontal diseases and systemic health.